Respuesta :

Answer:

(-9, 14)

Step-by-step explanation:

Let the column vector be represented as a = (3, 4) and b = (5, -2)

2a = 2(3,4)

2a = (6,8)

3b = 3(5, -2)

3b = (15, -6)

Take the difference 2a - 3b

2a - 3b = (6,8) - (15, -6)

2a - 3b = (6-15, 8 -(-6))

2a - 3b = (-9, 14)

Hence the column vector is (-9, 14)

We want to find 2a - 3b as a column vector, we will get:

[tex]2a - 3b = \left[\begin{array}{ccc}-9\\14\end{array}\right][/tex]

So we want to perform a sum (difference actually) of vectors, we have that:

[tex]a = \left[\begin{array}{ccc}3\\4\end{array}\right] \\\\\\b= \left[\begin{array}{ccc}5\\-2\end{array}\right][/tex]

Remember that when we multiply a vector by a scalar, each component gets multiplied by that scalar, so we have:

[tex]2a = \left[\begin{array}{ccc}2*3\\2*4\end{array}\right] = \left[\begin{array}{ccc}6\\8\end{array}\right] \\\\\\3b= \left[\begin{array}{ccc}3*5\\3*-2\end{array}\right] = \left[\begin{array}{ccc}15\\-6\end{array}\right][/tex]

Now we just perform the direct difference:

[tex]2a - 3b = \left[\begin{array}{ccc}6\\8\end{array}\right] - \left[\begin{array}{ccc}15\\-6\end{array}\right] = \left[\begin{array}{ccc}6 - 15\\8 + 6\end{array}\right] = \left[\begin{array}{ccc}-9\\14\end{array}\right][/tex]

If you want to learn more, you can read:

https://brainly.com/question/10435343